2020
DOI: 10.7717/peerj.9345
|View full text |Cite
|
Sign up to set email alerts
|

Learning to predict pain: differences in people with persistent neck pain and pain-free controls

Abstract: Background Learning to predict threatening events enables an organism to engage in protective behavior and prevent harm. Failure to differentiate between cues that truly predict danger and those that do not, however, may lead to indiscriminate fear and avoidance behaviors, which in turn may contribute to disability in people with persistent pain. We aimed to test whether people with persistent neck pain exhibit contingency learning deficits in predicting pain relative to pain-free, gender-and age-matched contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…22,46 For instance, impaired differential fear and contingency learning has been found in several pain conditions, such as fibromyalgia, chronic hand pain, or chronic neck pain. 23,30,47,48 Of interest, these patient groups showed not only impaired threat learning but also reduced safety learning. Patients with irritable bowel syndrome, on the other hand, displayed enhanced safety learning compared with healthy volunteers.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…22,46 For instance, impaired differential fear and contingency learning has been found in several pain conditions, such as fibromyalgia, chronic hand pain, or chronic neck pain. 23,30,47,48 Of interest, these patient groups showed not only impaired threat learning but also reduced safety learning. Patients with irritable bowel syndrome, on the other hand, displayed enhanced safety learning compared with healthy volunteers.…”
Section: Introductionmentioning
confidence: 93%
“…A recent study found reduced differential learning in patients with persistent neck pain, with lower CS + and higher CS − pain expectancies compared with those in healthy individuals, but comparable extinction rates. 23 One reason for these inconsistent findings might be the sample sizes of these studies, which were rather small (ie, N = 30 or lower) for an investigation in a highly heterogeneous clinical population.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, one study demonstrated that conditioned pain expectancy was greater when sensory information about location of the body part in pain was less precise (286). There is also experimental data demonstrating that the specificity of fear responses appears to be affected by the somatotopic precision of the body part (287) and that people with chronic pain may present a less precise US-expectancy and fear learning than control subjects (239,288,289), which partially strengthens the second assumption of the IH.…”
Section: Fear and Avoidance Behaviorsmentioning
confidence: 80%
“…increased arousal, vocalizations, flight or freezing, muscle startles) to contexts and sensory cues that preempt painful situations (25,142,240,241,244,245). However, as musculoskeletal pain is usually perceived during the execution of voluntary movements, individual with musculoskeletal pain may learn to fear and avoid movements perceived as harmful (144,239,(246)(247)(248)(249)(250)(251)(252)(253)(254).…”
Section: Fear and Avoidance Behaviorsmentioning
confidence: 99%
“…For example, generalization of fear to safe stimuli has been observed in several clinical populations such as people with panic disorder , generalized anxiety disorder (Lissek et al, 2014), and post-traumatic stress disorder (Lissek & Grillon, 2012). Similarly, whereas healthy participants were found to exhibit the expected fear generalization gradient, which decreases from the CS+ to CS-, people with fibromyalgia (Meulders, Meulders, et al, 2017a), chronic unilateral hand pain and chronic neck pain (Harvie et al, 2020), have been shown to exhibit flatter gradients with higher pain-expectancy towards GSs similar to the CS-. In another study, people with fibromyalgia showed less differential fear generalization between GSs similar to the CS+ and those similar to the CS-, in comparison to healthy control participants .…”
Section: Perceptual Fear Generalizationmentioning
confidence: 99%